The study of the abiloity of soy isolates of different trademarks to interact with water molecules - Fursik, Oksana; Bandura (Kuzmyk), Uliana; Sviatnenko, Roman; Marynin, Andriy; Strashynskyi, Igor; Pasichnyi, Vasyl (My University, 2021)
The established ability of soy isolates to absorb and hold water molecules was mainly due to the predominant amount of globular proteins, which showed a high ability to hydrate, provide high solubility, viscosity of experimental systems and they were characterized by high functional and technological properties (FTP): water-binding, fat-absorbing and emulsifying abilities, were able to form gels, structured matrices, stabilize emulsions, and also have high solubility, salt and heat resistance. This is one of the indicators which helps to combine their physical characteristics with raw meat materials. Due to the complex of properties, soy isolates remain one of the best protein preparations for the production of meat products.
Keywords: soy isolates; water molecules; кафедра технології молока і молочних продуктів; кафедра технології м’яса і м’ясних продуктів; соєві ізоляти; молекули води